Effect of six weeks of whole-body vibration in treatment of postnatal constipation - Eman Abd Elfatah Elhosary; Doaa Rafat ElAzab; ElSayed Mohammed Hanoura; Eman M Othman (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the efficacy of whole-body vibration in the treatment of postnatal constipation. Method: The prospective, randomised, single-blind, pre-post, controlled trial was conducted from December 2020 to May 2021 at the outpatient clinic of the Obstetrics and Gynaecology Department, Kafrelsheikh University Hospital, Egypt, and comprised women with complaint of postnatal constipation. They were randomised into two groups. Group A was subjected to whole-body vibration in addition to diet instructions, pelvic floor exercises and static abdominal exercises for six weeks. Group B was subjected to pelvic floor exercises, static abdominal exercises and diet instructions. Constipation symptom questionnaire and patient assessment of constipation quality of life questionnaire were used at baseline and post-intervention. Data was analysed using SPSS 25. Results: Of the 40 women, 20(50%) were in each of the 2 groups. Group A mean age was 24.88±2.22 years, while it was 24±2.25 years in Group B. Age, height and body mass index were not significantly different between the groups (p>0.05). There was significant improvement in Group A quality of life and constipation severity (p<0.05). Conclusion: Whole-body vibration had positive impact on postpartum women’s constipation symptoms and quality of life. Keywords: Pelvic floor, Vibration, Constipation, Postpartum period, Diet, Postnatal women.